The ethnography of tourism Edward Bruner and beyond - Leite, Naomi M.; Castañeda, Quetzil E.; Adams, Kathleen M. (The anthropology of tourism: heritage, mobility, and society, 2019)
"What does it mean to study tourism ethnographically? How has the ethnography of tourism changed from the 1970s to today? What theories, themes, and concepts drive contemporary research? Thirteen leading anthropologists of tourism address these questions and provide a critical introduction to the state of the art. Focusing on the experience-near, interpretive-humanistic approach to tourism studies widely associated with anthropologist Edward Bruner, the contributors draw on their fieldwork to illustrate and build upon key concepts in tourism ethnography, from experience, encounter, and emergent culture to authenticity, narrative, contested sites, the borderzone, embodiment, identity, and mobility. With its comprehensive introductory chapter, keyword-based organization, and engaging style, The Ethnography of Tourism will appeal to anthropology and tourism studies students, as well as to scholars in both fields and beyond"-- Provided by publisher.